Immanent Spirituality of Modernity - Jasiński, Karol (Studia Warmińskie, 2023)
The purpose of this paper is to characterize the fundamental manifestations of contemporary immanent spirituality, that is, spirituality that has no reference to the transcendent personal God or institutional religion, but is confined within the boundaries of the natural world. The paper consists of two parts. In the first one, the concepts of religion, religiosity and spirituality are clarified. Particular attention was paid to the differences in the classical and modern concept of spirituality. The second part presents two basic forms of immanent spirituality, often interrelated, which are the relationship with the natural world (cosmic feeling of unity, discovering the complexity of the world, experience of numinosum, intuition of ultimate reality) and the experience of the human subject (diversity of mental states, affirmation of human dignity, questioning of subjectivity).